Allegorical interpretation of the role of philosophy in the discourse of Philo and Ibn Rushd - Ishak, Mohd. Shuhaimi (Routledge, 2012)
Instead of dismissing traditional mythology and poetry as heresies, Greek philosophy introduced a methodology of understanding known as allegory. Philo of Alexandria (20 BC–50 AD) was one of the first to employ allegory for understanding religious scriptures whose writings survived in the Christian traditions. In the Arab world, the philosopher Ibn Rushd (520–595/1126–1198) initiated the same method of commentary with his demonstration of the essential harmony between philosophy properly understood and scripture properly interpreted. This essay posits that Greek philosophy laid down a common tool for understanding the scriptures that exist in the Christian and Muslim traditions.